1981
DOI: 10.1111/j.1600-0447.1981.tb02456.x
|View full text |Cite
|
Sign up to set email alerts
|

The need for long‐term neuroleptic treatment in schizophrenia

Abstract: The need for long-term neuroleptic treatment in nuclear schizophrenia depends on several factors, including the type of chronic schizophrenia, the phase of the disease, and the patient's total social situation. A neuroleptic drug withdrawal study demonstrated a need for further neuroleptic treatment for survival in the community even when the most symptom-free and socially best adapted chronic schizophrenics were considered. Prevention of relapse can apparently be achieved with lower neuroleptic doses than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Although antipsychotics are effective for the treatment of schizophrenia, many patients do not respond to the first antipsychotic prescribed (1)(2)(3). Patients without a response on a second antipsychotic trial are typically considered treatment resistant (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Although antipsychotics are effective for the treatment of schizophrenia, many patients do not respond to the first antipsychotic prescribed (1)(2)(3). Patients without a response on a second antipsychotic trial are typically considered treatment resistant (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Another study found relapse rate of 41% among those who continued quetiapine versus 79% who discontinued the medication at 1 year (Hui et al, 2013b). A number of studies and reviews converge to underscore the importance of poor adherence (or formerly compliance) in schizophrenia although they may differ to point out other risk factors (Dencker, 1981;Hogarty, 1993;Kissling, 1994;Gaebel, 1997;Kane, 1997;Mwaba and Molamu, 1998;Csernansky and Schuchart, 2002;Bradford et al, 2003;Barnes, 2004;Heller et al, 2006;Schooler, 2006;Kazadi et al, 2008;Kim et al, 2008;Ascher-Svanum et al, 2010;Xiang et al, 2011;Schennach et al, 2012;Hui et al, 2013a). The study by Caseiro et al (2012) for instance identified non-adherence as the sole offender with a hazard ratio of 4.8 for relapse.…”
Section: Risk Factors Of Relapsementioning
confidence: 99%
“…Diğer olarak sınıflandırılan gurupta ise 5 IQ sorunu, 1 cinsel işlev bozukluğu, 2 kişilik bozukluğu, 3 davranım bozukluğu, 7 çevresel stresör (eksen-4), 1 kekeleme ve 8 vitamin B-12 eksikliği saptanmıştır. (Tablo A-2) Antipsikotik tedavi, etkin şizofreni tedavisinin esas kısmını oluşturmaktadır [10][11][12]. Tipik antipsikotikler 1950'lerden itibaren kullanılmaktadır.…”
unclassified